(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Medical waste has a dangerous effect on environment. The mismanagement of it may be a significant risk factor for diseases transmission, in developing countries. This factor rose up with the increasing generation rate of medical waste. The study was conducted from October to December 2012 on one public hospital, twelve private hospitals and clinic and seven diagnostic centres of Jessore municipality of Bangladesh, where there has been no rigorous estimation of medical waste generation on the basis of scientific way. The study includes generation rate, existing management system and problem of medical waste. A convenience random sampling technique was followed to collect data. Actual measurement was done by digital weight machine to know about waste generation from the different sections of HCEs and a pre - structured questionnaire about the existing medical waste management. Visual field observation was also done to acquire the actual information. The research focused on the average generation rate of the studied HCEs was 1.59 kg/bed/day, 0.49 kg/patient/day and 0.11 kg/test/day. The generation rate in public hospital was 2.02 kg/ bed/ day, 0.49 kg/patient/day and 0.133 kg/test/day. The generation rate was 1.36 kg/bed/ day, 0.54 kg/patient/ day and 0.086 kg/test/day and 0.33 kg/patient/day and 0.168 kg/test/day in private clinic and diagnostic centre respectively. Result prevailed that unsat isfactory management practice observed on the basis of environmental safety. Adequate amount of selected colored dust bin, regular monitoring, arrangement of training, regular assessment of HCEs by government through the specialist, implementing of rules and regulations will be needed for improving existing medical waste management in the study area. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22115 J. Environ. Sci. & Natural Resources, 6(2): 181-189 2013